Advancing Perovskite Solar Cells: Addressing Stability, Scalability, and Environmental Challenges - Waheed Zaman khan; Mehwish Nazar; Bilal Younis; Mahnoor; Hussain Akbar; Saeed Ahmad; Rizwan Rustam; Iqra Akram; Fatima Munir (Dialogue Social Science Review (DSSR), 2024)
PSCs or perovskite solar cells are revolutionizing the whole renewable energy field by possessing low cost of production yet high efficiency. The achievement of perovskite cell efficiencies has reached over 25%, an important milestone for the technology as it was initially introduced into practical light absorbers within photovoltaic devices. Improvements in materials, engineering of interfaces, and techniques of fabrication have led to this development. This study summarises the latest developments in PSC research, emphasizing new developments in material stability, encapsulating techniques, and the creation of lead-free substitutes to improve environmental safety. We also consider scalable manufacturing techniques that address PSCs' environmental impact and enable mass production, such as roll-to-roll printing. The possibility of being integrated with energy storage systems and localized energy solutions makes PSCs important to assist in sustainable energy transitions, especially in underserved areas. Future research in this area is expected to overcome the current issues of stability, scalability, and recycleability, ensuring that PSC technology will be a contributor to meeting the world's energy demands and mitigating climate change.